IMPROVEMENT OF MANAGEMENT MECHANISMS OF GENERAL SECONDARY EDUCATIONAL ORGANIZATIONS - Абдулахадова, Шохида (АКТУАЛЬНОЕ В ФИЛОЛОГИИ, 2021)
This article discusses the current state of improvement of management mechanisms of general secondary education institutions and the necessary conditions for modern effective development, as well as the current issues of identifying and using opportunities for student-centered education in this process. Also, to implement measures to create opportunities for quality education in the system of general secondary education in accordance with international best practices and modern requirements of society, to strengthen the material and technical base of public education and increase the efficiency of budget funding, to create additional conditions for youth education the current view of consistent reforms. At the same time, the current state of general secondary education is analyzed in terms of the need to create mechanisms for the rapid elimination of systemic problems and shortcomings in their activities, to reduce the gap in logistics and quality of education in rural and urban schools and to create equal conditions for education. The results are given.